Rehabilitation in peripheral non femoral fractures: a review - Mangone, Giuseppe (CIC Edizioni Internazionali, 2010)
This paper is a short review of the available information on peripheral non femoral fractures (PNFF) which are strictly related to osteoporosis. Particular attention is focused on wrist fractures in view of their frequent occurrence as indicated by world wide statistics. Of special interest is the definition of risk groups (old age), risk areas (developed countries) and risk factors. Reference is made to 2008 WHO guidelines for fracture risk assessment. PNFF are a serious concern to health authorities because their high incidence in constant growth, causes a serious burden on the health budget. The pathway of patient care is described, from initial evaluation (including bone fragility, multi-morbidity and risk factors) to specific diagnosis and treatment. The multiplicity of etiological factors involved requires multidisciplinary approach. This aspect justifies the importance given to rehabilitation, which is the longest part of patient care and is strictly connected to preventive measures. There is ample reference to falls, to exercises, to appropriate sports, to complications and to active and passive mobilization. The paper suggests research in areas related to PNFF, to health economics, epidemiology, prevention, health education, training and multidisciplinary coordination.